Euler characteristic of Tango bundles - Nguyen Hong Cong (2023)
We are interested in a vector bundle constructed by Tango. The Tango bundle is an indecomposablevector bundle of rank n−1 on the complex projective space Pn. In particular, we show that theEuler characteristic of the Tango bundle on Pn is equal to 2n−1